RELATION BETWEEN SCENES AND LYRICS IN ROSÉ’S MUSIC VIDEO: A SEMIOTIC ANALYSIS - Lathifah Dinda Srijati; Ika Oktaria Cahyaningrum (Translation and Linguistics (Transling), 2024)
Rosé is a female soloist who debuted in early 2021 with the release of her single album, -R-. The album includes two songs and two music videos on it. The music videos themselves consisted of gestures that came along with the lyrics that Rosé sang. Listeners are expected to understand the message behind the gestures and words in the music videos, as well as the denotative and connotative meanings, to better understand it. That being said, the researcher had to take Relation Between Scenes and Lyrics in Rosé’s Music Video: A Semiotic Analysis for the research. This study used a semiotic approach to analyze the gestures in the scenes and looked at the denotative and connotative meanings by Roland Barthes’s theory. Data is analyzed with the descriptive qualitative method. The analysis explains the relation between lyrics and scenes along with denotative and connotative meanings. This study aims to deliver the meaning and give the listener a better understanding of the album to the listener.